KEBIJAKAN KRIMINALISASI TERHADAP APARAT PENEGAK HUKUM YANG TIDAK MENERAPKAN ASAS PRADUGA TAK BERSALAH DALAM SISTEM PERADILAN PIDANA - Mohamad Ikrom; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Code of Criminal Procedure Code Law Act 8 of 1981 on the Code of CriminalProcedure Code, is actually one of the formal rules for the law officers to give suspects rightsas civilized human beings in dealing with criminal law. However, the data shows that theoccurrence of violations of the presumption of innocence during the process of finding evidenceis a very high case as the top of the iceberg. Therefore, as an effort to overcome violence andviolations of the presumption of innocence in the investigation process and the importance ofcreating a paradigm new law, in order to change the public's perspective on the lack of trustin law enforcement officers. When a suspect is determined, it is necessary to carry out the ideaof a criminal sanction law as regulated in Article 18 of Law Act 9 of 1999 on the Press topresent a law that is more appropriate in responding to modernization needs.This research is normative legal research supported by secondary data, carried out bymaking library materials the main focus. Also called doctrinal legal research, namely legalresearch that uses data based on library research by taking quotes from reading books, orsupporting books that have something to do with the problem to be studied. Thus, this studyuses secondary data sources consisting of primary, secondary, and tertiary legal materials.This study also uses qualitative data analysis and produces descriptive data.From the results of the discussion and research conducted, there are severalconclusions obtained, namely: First, the imposition of sanctions on law enforcement officerswho do not apply the principle of the presumption of innocence is not regulated at all in theIndonesian positive legal system, only regulated by the application of the principle ofpresumption of innocence in Indonesia. Law Number 48 of 2008 concerning Judicial Power,so that cases of violation of the rights of suspects in the fact-finding process become normalfor the apparatus. Second, the increase in criminal sanctions in the form of imprisonment andfines is an idea that is formulated by taking into account the views of life, awareness and legalideals, as well as the philosophy of the Indonesian nation originating from Pancasila and thePreamble to the 1945 Constitution of the Republic of Indonesia.Keywords: Ideas – Criminal Sanctions – Presumption of Innocent